Decolonizing the Spirit in Education and Beyond: Resistance and Solidarity - Wane, Njoki Nathani; Todorova, Miglena S; Todd, Kimberly L (Palgrave Macmillan, 2021)
This multidisciplinary collection probes ways in which emerging and established scholars perceive and theorize decolonization and resistance in their own fields of work, from education to political and social studies, to psychology, medicine, and beyond
Keywords: 1-Cinéma; 1-Histoire de l'art; 1-Jeux vidéo; 1-TV; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 5-Auteur.rice; 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Auteur.rice noir.e; 5-Autrice; _Nettoyé

Towards Diversity: Interventions in Curriculum and Pedagogy of an Introductory Game Design Course - Hanli, Geyser (DiGRA/FDG '16 - Abstract Proceedings of the First International Joint Conference of DiGRA and FDG, 2016)
Transformation and the decolonization of the curriculum, modes of teaching, and classroomare key concerns in South African Higher Education. In game design education this need is exacerbatedby the slow pace of diversification in both academia and the industry.This paper presents a close analysis of interventions undertaken into an introductory game design course to address the difficultiesof diversification across racial, genderand economic divides. The results of the interventions are assessed, and recommendations for future adjustments to the course in aid curricular decolonization is are made.
Keywords: 1-Jeux vidéo; 2-Genre et sexualité; 2-Pédagogie décoloniale; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Afrique (corpus analysé); 4-Afrique (lieu de production du savoir); 5-Autrice; _Nettoyé